Creating High Levels of Gas Production From Waste Mushroom Substrate Pellets - Sirikul Saengsuwan; Somchai Kritpolwiwattana (AGRIVITA, Journal of Agricultural Science, 2019)
This study was to investigate the use of waste mushroom substrate (WMS) material, and waste mushroom substrate pellets (WMSP), with two catalysts (K2CO3 and CaO), as biofuel feed to produce CH4 in an updraft gasifier. The WMS was made from composted rubber wood chips which had been used for mushroom bed log culture, and pelletizing the WMS (WMSP) to create a biomass with a greater bulk density than the normal WMS. The gasification was determined in the high temperature range of 400-800 0C by dry fuel feeding at the rate of 25 kg/ha. The results showed that the optimum operation was achieved with WMSP with K2CO3 as the catalyst, at ER = 0.11. The combination of WMSP and K2CO3 produced more CH4 at 62.2 and 15.27% than single WMS and WMSP, respectively. WMSP with CaO as the catalyst produced 29.65 % less CH4 than WMSP. Based on gasification equation, CO produced from WMSP was calculated 24.116 % wt, 31.52% wt from WMSP with K2CO3 and 19.21% wt from WMS. The amount of gas produced from the available waste material as the biomass was sufficient to meet all heating requirements of the mushroom production.